Labersa Toba Hotel & Convention Centre Employee Performance Assessment Decision Support System Using Multi Factor Evaluation Process - Purba, Chandra; Sitorus, Marjones Pardomuan; Sinulingga, Ribka (Marcha Institute, 2024)
In improving the quality of public servants at Labersa Toba Hotel & Convention Centre, in this case employees, the leadership has actually made various innovations. One of them is giving awards to employees who have achievements. However, the performance assessment that has been carried out so far does not meet the standard criteria of an organization's work, because performing performance calculations is still limited to recapitulation of attendance by way of manual attendance recapitulation which takes a long time. This, of course, in addition to taking a long time, also allows for calculation errors. Employee performance appraisal related to the successful implementation of duties and personnel capabilities does not affect the improvement of service quality to the community. MFEP is a quantitative method that uses a weighting system. In multi-factor decision making, decision makers subjectively and intuitively weigh various factors that have an important influence on their chosen alternative. For strategically influential decisions, it is preferable to use a quantitative approach such as MFEP, from 10 Candidates calculated with the MFEP of candidates who having the highest evaluation weight is Candidate 3 (K3) with an Evaluation Weight Value = 79.00.